A New Method for Solving the Mass and Heat Transfer Process in Steam Flooding - Wang, Fei (Frontiers in Energy Research, 2022)
Nowadays, Heavy oil is becoming an increasingly significant part of the future energy strategy, and understanding how to effectively mimic the steam flooding flow process as a way for developing steam flooding is critical. The purpose of this article is to create a mathematical model of steam flooding with coupled permeability and heat fields, and then to solve the mathematical model numerically using the weighted least squares meshless approach. This paper constructs a one-dimensional conceptual model of a steam flooding reservoir to demonstrate the method's soundness. The model is calculated at 80%, 90%, and 100% steam dryness, and it is discovered that the temperature distribution throughout the reservoir remains almost identical, with the exception of the gas saturation distribution. The porosity of the model was subjected to sensitivity analysis in this paper. Porosity, it is discovered, has a direct effect on the leading-edge distribution of gas-bearing saturation and temperature. The calculation is consistent with objective factual perception, which demonstrates the accuracy and stability of the method used in this work.